194k views
4 votes
Use completing the square to solve the equation x2 - 10x = -8.

Which equation is used in the process?

x 2 - 10x + 25 = 17
x 2 - 10x + 25 = -8
x 2 - 10x - 25 = -33

2 Answers

3 votes

Answer:

The first person that told the answer has it correct so beleive the answer

Explanation:

User Grom
by
5.1k points
2 votes

Answer:

x^2 - 10x + 25 = 17

Explanation:

x^2 - 10x = - 8

Now x^2 - 10x = (x - 5)^2 - 25, so

(x - 5)^2 - 25 = -8

(x - 5)^2 = -8 + 25

x^2 - 10x + 25 = 17..

User Zarel
by
4.9k points